TRIM31 regulates chronic inflammation via NF-κB signal pathway to promote invasion and metastasis in colorectal cancer - Wang, Haiyu (Am J Transl Res, 2018)
Tripartite motif 31(TRIM31) is a new member of the E3 ubiquitin ligase family, which plays a role in many biological processes. It has been indicated that TRIM31 is strongly correlated with tumorigenesis. However, the impact of TRIM31 in colorectal cancer (CRC) and its underlying mechanisms are largely unknown. In this study, we found an increase in TRIM31 expression in CRC cells and a positive correlation between TRIM31 and CRC malignancy. Applying genetic interventions and cellular function tests, our results showed that TRIM31 acted as an epithelial-mesenchymal transition (EMT) inducer to promote CRC invasion and metastasis. Mechanical exploration revealed that TRIM31 mediated the upregulation of inflammatory cytokines TNF, IL-1β, and IL-6 through the NF-κB pathway, thus contributing to EMT in CRC progression. Collectively, we concluded that TRIM31 mediated chronic inflammation via the NF-κB pathway to promote invasion and metastasis in CRC. Therefore, we can infer that TRIM31 may be a valuable detective marker in primary CRC, and therapeutic intervention related to EMT suppression via TRIM31 can be a viable option for patients with advanced CRC.